An investigation in the VMI stock replenishment strategy in the Fast Moving Consumer Goods Industry: the benefits and the drawbacks for Nestle in the UK, supplier of food and drink products. - Kovlakidou, Evagelia (2007)
Tighter budgets and greater emphasis on customer satisfaction forces more and more companies to recognise that it is impossible to maintain all the necessary capabilities to successfully compete alone and are forced to redesign their networks and reassess their strategies. Nowadays competition is between supply chains rather than individual firms alone; therefore, companies engage in collaborative relationships, which can sometimes be hard to achieve. Information availability has an impact on the operational management of the supply chain. The optimal inventory policies for each supply chain partner will depend on the levels and methods of information sharing used between them. These strategic partnerships change the way information is shared and inventory managed within a supply chain, possibly eliminating the impact of the bullwhip effect. Information technology such as EDI, World Wide Web and RFID can prove to be a powerful tool to establish, maintain and/or strengthen relationships between supply chain partners in an attempt to improve overall the performance of a particular supply chain or system. Supply chain collaboration and integration enables companies to develop or use models for efficient replenishment of stock. Examples of such efforts/methods include Quick Response, Continuous Replenishment, Efficient Consumer Response (ECR), Vendor-Managed Inventory (VMI) and Collaborative Planning, Forecasting and Replenishment (CPFR). VMI has a certain set of requirements for its successful implementation. All parties involved in a VMI effort could enjoy benefits from it, however, the programme has some limitations. VMI concept is gaining ground in multiple industries. Nestle is currently engaged in a successful VMI relationship with one of the UK's largest retailers. The manufacturer has access to real demand data and is responsible for raising orders and replenishing stock at the customer's depots. Nestle treats VMI as part of its competitive strategy and it will continue to support such efforts in the future.